Penyuluhan Peranan Kemasan dan Labeling untuk Meningkatkan Nilai Tambah Produk Bagi Kelompok Usaha Masyarakat Program OVOP - Reinaldis Masi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2026)
This Community Service (PKM) activity aims to enhance the understanding of Micro, Small, and Medium Enterprises (MSMEs) regarding the importance of packaging and labeling in increasing the added value of products in areas implementing the One Village One Product (OVOP) program. Packaging and labeling serve as product identity as well as a medium for conveying information related to composition, safety, and usage, which contribute to attracting consumer interest and improving market competitiveness. The methods used in this activity include lectures, discussions, and experience sharing. The program was conducted over three days at Asa Larantuka Hotel, involving 40 MSME participants from East Flores, Sikka, and Lembata Regencies. The results indicate an improvement in participants’ understanding, as measured by a comparison of pretest and posttest scores, with an average increase of 30%. In addition, 75% of participants were able to develop simple packaging and labeling designs that met product information and visual appeal criteria. Therefore, this activity is effective in enhancing the capacity of MSME actors to develop packaging and labeling as a strategy to increase product added value.